A study on the service quality in Socso Bintulu / Samsiah Mohammad - Mohammad, Samsiah (2007)
I would like express my deepest gratitude to my advisor, Madam Ellen Chung Siew Mee for her guidance, comments and commitments which without her help, this project would not be successful. I would like also to extend my appreciation to my boss, Mr Dundang Anak Undong, my colleagues, my friends and also not forgotten to all the respondents who have helped me for providing all the relevant information.